(untitled) (Asian Journal of Ethnobiology, 2022)
Abstract. Gnahore E, Kouadio KR, Amba AJG, Kone M, Bakayoko A. 2022. Ethnobotanical survey of plants used by the riparian population of Banco National Park (Abidjan, Ivory Coast). Asian J Ethnobiol 5: 121-129. Situated at the "heart" of Abidjan, Banco National Park (BNP), Ivory Coast, is the rare relics of moist, dense rainforests coveted everywhere. This work was undertaken with an aim of identifying the plants most usually used by the riparian population of BNP in human food, animal food, and pharmacopeia. An ethnobotanical survey was carried out of the riparian population of the BNP. The method consists of an ethnobotanical survey realized among the inhabitants of the park and those of the surrounding urban districts. The method used was semi-structured interviews. This study targeted 294 people, including 20% men and 80% women, aged between 30 and 60. A total of 36 plant species from 34 genera and 28 families were recorded. Thirteen species were used in food, three fodder species, and thirty others used to treat several ailments in the area. Two of these plants have strong ratio utilization in human food: Myrianthus arboreus P.Beauv. (15.25%) and M. libericus Rendle (14%). Thus, in the area study, five species are respectively considered threatened and three species rare. Leaves (32.55%) and bark (20.93%) are the most used organ. Decoction (98%) was the most common traditional medicine preparation method. Indigenous knowledge distribution in the community showed significant differences (p<0.05) in the study groups for factors of age, sex, gender, and educational level. The number of resources used can seriously impact the forest negatively. It is urgent to adopt a lasting management plan for sustainable harvest for the safeguard and preservation of the plant cash of the BNP.